Effect of Bean Extract (Phaseolus vulgaris L) to LDL and Ox-LDL and Relation of Ox-LDL on LOX-1 Gene Polymorphism 3'UTR - Shahrul Rahman (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
Aim: To find out whether bean extract has effects on levels of LDL and Ox-LDL and relation of Ox-LDL onLOX-1 gene polymorphism 3'UTR188CT.Method: This research is true randomized experiment with a pretest - posttest design and control group.Samples were 35 subjects divided into 4 groups. Laboratory experiments using bean extract test affects LDL andplasma levels of Ox-LDL by Enzyme -linked Immunosorbent Assay (ELISA), test LOX-1 gene polymorphism3'UTR188CT with restriction enzyme. To evaluate effect of bean extract to LDL and Ox-LDL level werecompared with unpaired t-test. To evaluate difference of Ox-LDL level on LOX-1 gene polymorphism3'UTR188CT using ANOVA. Results: There was a decrease of LDL found in all treatment groups and elevatedlevels of Ox-LDL. TT genotype had higher levels of plasma Ox-LDL both before (49,9 ± 8,3 vs. CC 39.9 ± 19.4and CT 42,8 ± 61,2,p .648 ) and after treatment (60.3 ± 5.7 vs. CC 55.93 ± 12.6 and CT 53.9 ± 10.3, p .630) thanother genotype.Conclusion: Bean extract can lower LDL cholesterol although it can also increased plasma levelof Ox-LDL. TT genotype had higher levels of plasma Ox-LDL than other genotypes. Require further study toother antioxidants may have a beneficial effect by lowering the levels of Ox-LDL.